Esporotricose no Estado do Espírito Santo : um estudo de três décadas - Caus, Antonio Luiz de Oliveira (2013)
Introduction: Sporotrichosis is an infectious disease caused by Sporothrix schenckii, a dimorphic fungus that has worldwide distribution, usually localized at the skin and subcutaneous tissue of humans and animals. It is a rare condition and there are no data concerning its clinical or epidemiological features in Espírito Santo state, Brazil. Material and methods: Descriptive case-series study to determine the clinical and epidemiological aspects of patients with human Sporotrichosis seen at the Infectious Diseases Department of the Hospital Universitário Cassiano Antônio Moraes (HUCAM), Vitória, ES, from 1982 – 2012. Results: Among the 171 cases of human Sporotrichosis included, 80.70% were male, 89.16% were white and the median age founded was 33.5 (DQ: 24 - 74) years-old. All patients had direct contact with soil and plants in work or in their leisure activities. Most of the cases were from a specific mountainous region of the state, the Região Serrana. The duration of symptoms before the definitive diagnosis was, on average, of three months (SD: two – ten months) and the lymphocutaneous form was the most common manifestation (70.17%), followed by the fixed cutaneous form (28.65%). Laboratorial diagnosis was established in 93.75% of the cases by direct visualization of S. schenckii colonies when cultured in Sabouraud dextrose agar and the rest of them were diagnosed only by clinical features of the disease. Comparatively, aspirate with purulent and seropurulent contents from gummy skin lesions was the best way to collect clinical specimens for diagnosing the Sporotrichosis. Treatment with oral 25% Potassium Iodide solution was implemented for almost all patients (98,83%) successfully. Treatment loss to follow-up occurred in only 36 patients (21.05%). Conclusions: The relevance of this study rests on showing the characteristics of a disease that, despite its rareness, is endemic in Espírito Santo state, not very known and makes important differential diagnosis with other common conditions in this region.